Factors influencing the level of patients’ satisfaction with mental healthcare delivery in Tamale Metropolis: a multicentre cross-sectional study - Mariama Alhassan Dokurugu; Gifty Apiung Aninanya; Mustapha Alhassan; Robert Kokou Dowou; Dennis Bomansang Daliri (BMC Health Services Research)
Abstract Introduction Patient satisfaction is crucial in mental healthcare and its impact on treatment outcomes. Despite the global burden of mental disorders, there are limited research on client satisfaction, especially in Ghana. This study aimed to investigate factors influencing patient satisfaction with mental health care in the Tamale Metropolis. Methods A multicentre cross-sectional study was conducted involving 382 mental health service users in selected health facilities in the Tamale metropolis. A semi-structured questionnaire adapted from Patients Satisfaction Questionnaire (PSQ-18) was used to collect data on patients’ satisfaction with the mental health service. Data were analyzed using SPSS version 20 and both descriptive and inferential analysis was done. Results Overall, 54.7% of service users were satisfied with the mental health care received. Participants aged 20–29 years and those aged 50–59 years were significantly less likely to be satisfied compared to participants below 20 years. Residents of peri-urban (AoR = 0.03; 95% CI = 0.01–0.19) and rural areas (AoR = 0.02; 95% CI = 0.00–0.16) were less likely to report satisfaction than urban residents. Unmarried (AoR = 0.73; 95% CI = 0.01–0.77) and uneducated participants (AoR = 0.76; 95% CI = 0.01–0.91) were less likely to be satisfied with the mental health service. Financial factors and long waiting times were associated with decreased satisfaction. Access challenges, perceived provider attentiveness, and stigma within health facilities further reduced satisfaction odds. Conclusion There is a fundamentally favorable level of reception for mental health treatments, as evidenced by the fact that over half of the participants were satisfied with them. The findings indicate that there is still more room for improvement, especially when it comes to tackling systemic barriers and demographic variations to improve overall client experiences. Ghana Health Service and other partners should put in place interventions to enhance the delivery of mental health services.